Beyond Diversity: How Dietary Pattern Analysis Adds to Our Understanding of Diet Quality in Rural Nepal. - O'Hara, Corey. (Tufts University. Tisch Library., 2019)
Background: Dietary diversity scores are well-understood, validated indicators of diet quality in terms of micronutrient adequacy for individuals and of food security in terms of caloric access for households in low-income environments. The relationship between dietary diversity and quality/sufficiency is not as clear at the upper end of the spectrum, however, where components of higher-diversity diets may also be risk factors for negative health outcomes. In wealthier environments, by contrast, dietary pattern analysis is commonly used to identify combinations of foods consumed that have a relationship to human health outcomes. Methods: This study identifies dietary patterns in individual food consumption data from a clustered, controlled intervention trial in western Nepal and compares them with dietary diversity scores across a range of analyses. First, we identify factors associated with household and individual patterns. We assess the relationships of the patterns to diversity scores constructed from the same 24-hour recall dietary diversity survey data, and we describe differences in consumption between individuals consuming each pattern and those achieving minimum dietary diversity according to conventional indicators. Second, we look at associations between child dietary patterns and child anthropometry to determine whether pattern scores are more or less predictive of nutritional status than dietary diversity indicators. Third, we determine whether agricultural production, diversification, and marketing intervention, compared to marketing intervention alone, affects household dietary patterns over time. We assess the effect of intervention on dietary patterns as distinct from dietary diversity, and whether such pattern scores contribute additional information. Results: We find that dietary patterns convey useful information about dietary quality that is additional to what we learn from individual dietary diversity scores alone. We observe that indicators derived from dietary patterns identify a smaller group of individuals than minimum diversity scores and observe significant differences in diet between those consuming or not consuming each pattern who meet the minimum diversity threshold. We find that in this context, dietary patterns—but not dietary diversity—are associated with child weight-for-height, with a dairy/sweets pattern predicting lower rates of wasting and higher rates of overweight in children aged 6 to 59 months. Finally, we see that over time, agricultural intervention is positively associated with adoption of a varied dietary pattern, rather than the dairy/sweets pattern that is associated with negative outcomes. Conclusions: In this population, dietary pattern analysis contributes additional value to assessment of diet quality compared to use of dietary diversity indicators alone. Pattern analysis identifies commonly consumed combinations of foods, which can be useful in developing nutrition counseling interventions. Indicators developed from dietary patterns can identify individuals who are not consuming critical nutrient-dense foods despite meeting minimum diversity. Dietary patterns are associated with child anthropometry, which can help to identify vulnerable populations while informing future nutrition counseling interventions. Longitudinal analysis reveals that dietary diversity scores on their own may mask effects that can be revealed by analysis of dietary patterns.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Food Policy & Applied Nutrition.; Advisor: Beatrice Rogers.; Committee: Beatrice Rogers, Patrick Webb, and John Hoddinott.; Keywords: Nutrition, and Economics.